Taxonomy of mobile phone usage among Malay population in Segamat / Shaifudin Sulaiman ... [et al.] - Sulaiman, Shaifudin; Hashim, Nur Hayyu Hams; Mohd Hairullah, Siti Fatimah; Manap, Zulaida (2014)
The case study contains a full research about the activities being done by the Malay residents in Segamat on their mobile phone from different groups of age which started with the age 7-12, 13-19, 20-30, 31-40, and 40 years old and above. Segamat located in the north of the state of Johor in Malaysia and bordering Negerj Sembilan on the west while Pahang on the north. It was located roughly 172 kilometres from Johor Bahru, the capital city of Johor State. There were variety of communities in Segamat consist of Malay, other Bumiputera, Chinese, India, others and Non-Malaysian citizens. It this research also the researchers provide the data analysis collected from the research which explained the pattems of mobile phone usage among the Malay population in Segamat which the researchers focused at Batu Anam Keywords: Mobile phone, Segamat, Malay population